PENGARUH INTERNAL AUDIT DAN SPESIALISASI AUDIT TERHADAP AUDIT DELAY - Astri Larasati (2020)
This research is a quantitative study that aims to examine the effect of internal audit and audit specialization on audit delay. In this study, Audit Delay is measured based on the length of days needed to receive an independent auditor's report on the fiscal financial statements, in review from the closing date of the company's books as of December 31 until the date recorded on the independent auditor's report. The sample in this study amounted to 427 companies listed on the Indonesia Stock Exchange in 2018, the sample in this study using purposive sampling. Hypothesis testing in this study uses Multiple Regression Analysis with SPSS program, with a significance level of 5%. The results of this study found that (1) internal audit has a significant effect on audit delay. (2) audit specialization does not have a significant effect on audit delay.